Civic Participation in Public Sector Education: A Critical Policy Analysis of the School System in Chile - Francisca Alvarez-Figueroa; Christopher J. Rees (Administrative Sciences, 2025)
The main aim of this study is to examine how education policies in the public sector of Chile have shaped civic participation among stakeholders in the education sector. We address two complementary research questions. First, has the implementation of top-down State-level education policies created practice-oriented opportunities for key stakeholders to collaborate with the distinct governing bodies operating in primary and secondary schools in Chile? Second, to what extent have top-down State-level public sector education policies in Chile affected stakeholders’ levels of influence and participation in decision-making at the local level? To address these questions, the study involves a critical policy analysis of educational policies enacted in Chile between 1990 and 2022. The findings reveal that Chile’s education policies were: (a) characterized by a neoliberal orientation to service delivery and (b) positively affected some aspects of civic participation of stakeholders in education at the local level. Notably, the majority of governing bodies that promoted policy-driven civic participation were based in fully funded public schools. This paper contributes to understanding civic participation in a deeply neoliberal context and, through critical analysis, highlights how the power and collaboration of schools’ governing bodies in Chile are limited and differentiated by the nature of their funding.